Parental Income As A Moderator Of The Influence Of Financial Literacy, Hedonic Lifestyle, Locus Of Control On Students' Financial Behavior (Case Study Of Students In The Special Region Of Yogyakarta) - Sri Lestari Yuli Prastyatini; Susanna Eka Rakhmani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyse the factors that influence student financial behaviour among 71 university students in the Yogyakarta area. The method applied in this study is multiple linear regression using primary data obtained from distributing questionnaires using google forms through the WhatsApp application. The results showed that Financial Literacy has a positive effect on Student Financial Behaviour, Hedonic Lifestyle and Locus of Control have a negative effect on Student Financial Behaviour. Parental income is able to weaken the relationship between financial literacy and hedonic lifestyle on student financial behaviour. However, it is able to strengthen the relationship between locus of control on student financial behaviour. This study is expected to be able to prove how Parental Income acts as a moderating variable that affects Financial Literacy, Hedonic Lifestyle and Locus of Control on Student Financial Behaviour. This study uses Parental Income as a moderating variable with students as research subjects. Hopefully, this research can provide deeper insights to students about the importance of the ability to control and manage personal finances, so that they can create better financial stability.